Школьные истории: [рассказы] / художники: В. Дунько [и др.] - Дунько В. (Библиотека начальной школы, 2017)
Экземпляры: (20230131) / Инвентарный номер: 40412 / Цена: 112.70 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Ш 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=411.2)6